The role of exclusive breastfeeding on sIgA and lactoferrin levels in toddlers suffering from Acute Respiratory Infection: A cross-sectional study. (May 2022) - Fatimah,; Massi, Muhammad Nasrum; Febriani, Andi Dwi Bahagia; Hatta, Mochammad; Karuniawati, Anis; Rauf, Syahrul; Wahyuni, Sitti; Hamid, Firdaus; Alasiry, Ema; Patellongi, Ilham; Permatasari, Tria Astika Endah; Farsida,
Abstract: Secretion of Immunoglobulin A (sIgA) and lactoferrin is a nutrient content in breast milk that can increase immunity in preventing infectious diseases such as Acute Respiratory Infection (ARI). This research aims to determine the role of exclusive breastfeeding (EBF) on sIgA and Lactoferrin levels in toddlers suffering from ARI. A cross-sectional study was conducted on 124 toddlers under five from January–July 2021. Toddlers were selected using a purposive technique sampling from three Community Health Centers in Central Jakarta. Data were analyzed using t -test and ANOVA. The history of immunization, EBF, and frequency of ARI was significantly associated with levels of sIgA and lactoferrin. Parity only correlated with sIgA but not with lactoferrin levels. Maternal and toddlers' age, gender, and nutritional status were not significantly related to sIgA and lactoferrin levels. There is a significant (p-value <0.001) difference in the mean protein sIgA and lactoferrin levels in toddlers who were given EBF with ARI frequency <2 times and toddlers who were given EBF with ARI frequency ≥2 times. Toddlers who were exclusively breastfed with ARI frequency <2 times had higher levels of sIgA and lactoferrin (188901.77 pg/ml and 262.32 ng/ml, respectively) compared to infants given EBF with ARI frequency ≥2 times (136683.47 pg/ml and 181.49 ng/ml, respectively). History of immunization was also significantly (p-value <0.05) associated with levels of sIgA and lactoferrin in infants with ARI. The content of sIgA and lactoferrin in breast milk and immunization can increase the body's immune system in toddlers suffering from ARI. Highlights: Breast milk contains sIg A and lactoferrin, which act as antibodies to increase immunity in toddlers suffering from ARI. Exclusive breastfeeding significantly increased sIgA and lactoferrin levels in toddlers suffering from ARI. Toddlers who are exclusively breastfed with ARI frequency < two times have higher levels of sIga A and lactoferrin than infants who are not exclusively breastfed and suffer from ARI ≥ two times.